Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/s004320100273
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study on VEGF expression in endometrial carcinoma – comparison with p53 expression, angiogenesis, and tumor histologic grade

Abstract: VEGF expression was not a single specific indicator of angiogenesis in endometrial carcinoma, whereas it was significantly correlated with p53 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2003
2003
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…The staining methods were described elsewhere (Fujisawa et al 2001;Kato et al 2003;Kyushima et al 2002;Watanabe et al 2002). In brief, the antibodies used were those for Ki-67 (rabbit polyclonal, 1:50, Dako, Kyoto, Japan), cdk2 (rabbit polyclonal, 1:2000, Santacruz, Calif., USA), cyclin A (clone 6E6, 1:100, Novocastra), cyclin D1 (clone DCS-6, 1:80, Oncogene, Mass., USA), cyclin E (clone 13A3, 1:40, Novocastra), p27 (clone 1B4, 1:200, Novocastra) and p53 (clone DO-7, 1:80, Novocastra).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The staining methods were described elsewhere (Fujisawa et al 2001;Kato et al 2003;Kyushima et al 2002;Watanabe et al 2002). In brief, the antibodies used were those for Ki-67 (rabbit polyclonal, 1:50, Dako, Kyoto, Japan), cdk2 (rabbit polyclonal, 1:2000, Santacruz, Calif., USA), cyclin A (clone 6E6, 1:100, Novocastra), cyclin D1 (clone DCS-6, 1:80, Oncogene, Mass., USA), cyclin E (clone 13A3, 1:40, Novocastra), p27 (clone 1B4, 1:200, Novocastra) and p53 (clone DO-7, 1:80, Novocastra).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Positive staining was evaluated by counting approximately 1,000 cells in high-power fields and was expressed as the labeling index (LI), which was regarded as the percentage of positive nuclei. The result of skp2 expression was compared with those of p27, Ki-67, cdk2, cyclin A, cyclin D1, cyclin E, p53 and PTEN, which had been analyzed in our laboratory Akaboshi et al 2001;Kyushima et al 2002;Nishimura et al 2004;Kato et al 2003;Fujisawa et al 2001;Kimura et al 2004). …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…VEGF expression did not correlate with histological grade or the number of microvessels in the tumour area. They concluded that further follow-up study was mandatory to clarify the role of VEGF expression as a prognostic factor in endometrial carcinoma [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Fine et al [11] showed in a small patient series that VEGF and its receptors fl t-1 and KDR/fl k-1 did not correlate with the incidence of metastases, recurrence and survival. Fujisawa et al [12] conducted a study comparing VEGF expression, angiogenesis, p53 expression and tumour histological grade. VEGF expression did not correlate with histological grade or the number of microvessels in the tumour area.…”
Section: Introductionmentioning
confidence: 99%